Experimental evaluation of large-scale dual-core self-centering braces and sandwiched buckling-restrained braces. (1st June 2016) - Chou, Chung-Che; Chung, Ping-Ting; Cheng, Yu-Tsen
Highlights: The paper presents cyclic test results of large-scale DC-SCBs and SBRBS. A total of three SCBs and SBRBs that were about 7.5 m long were tested. Yielding of steel tendons on the cyclic behavior of the SCB was evaluated. DC-SCB had low residual deformation and one-third energy dissipation of SBRB. Abstract: This paper presents structural characteristics of large-scale dual-core self-centering braces (DC-SCBs) and sandwiched buckling-restrained braces (SBRBs) in a series of cyclic tests. The DC-SCB has a flag-shaped hysteretic response with high axial stiffness and minimal residual deformation, exhibiting a self-centering mechanism. The SBRB as conventional BRBs has much higher energy dissipation capacity than the DC-SCB, but larger residual deformations are expected for structures equipped with SBRBs. The primary objective of the research was to conduct experimental studies that established a direct comparison basis between DC-SCBs and SBRBs designed with similar axial capacity and length. Three SCBs and SBRBs that were about 7.5 m long and had maximum axial forces from 1500 to 6000 kN were tested to evaluate their cyclic behavior and durability. In general, these tests have shown that the DC-SCB and SBRB exhibit robust cyclic performances with good deformation capacity and durability. The axial elastic and post-elastic stiffnesses of DC-SCB were around two and five times those of SBRB, indicating that the DC-SCB is more effective to resist lateral forces than the SBRB in structures, but the energy dissipation of DC-SCB was around one-third of that of SBRB.